2011
DOI: 10.2169/internalmedicine.50.5686
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Gas-Forming Liver Abscess with Diabetes Mellitus

Abstract: A 43-year-old man was admitted to our hospital with right hypochondriac and epigastric pain. An abdominal radiograph showed a large niveau in the right subphrenic space. An abdominal CT scan demonstrated a large liver abscess (diameter, 13 cm) with gas formation. Klebsiella pneumoniae cells were isolated from the abscess, and the patient was treated with antibiotics and percutaneous drainage. It is very important to treat gas-forming liver abscess immediately, because subsequent bacteremia and septic shock are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Pyogenic liver abscesses are often polymicrobial, and E. coli and Klebsiella pneumoniae are the two most frequently isolated pathogens 6. Mortality is ∼15%, but it depends on the underlying cause and the pre-existing hepatic disease 7. Broad-spectrum antibiotic therapy, percutaneous or surgical drainage and, if possible, control of the primary source are the main keys to preventing a dramatic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Pyogenic liver abscesses are often polymicrobial, and E. coli and Klebsiella pneumoniae are the two most frequently isolated pathogens 6. Mortality is ∼15%, but it depends on the underlying cause and the pre-existing hepatic disease 7. Broad-spectrum antibiotic therapy, percutaneous or surgical drainage and, if possible, control of the primary source are the main keys to preventing a dramatic outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, some clinical differences exist. Statistically, among patients with PLA, the incidence of bacteremia and septic shock in GFPLA patients is higher than that in non-GFPLA patients 5 . A large case series study from Taiwan which involved 83 GFPLA patients and 341 non-GFPLA patients showed that septic shock occurred in 32.5% of patients with GFPLA while it occurred in only 11.7% of patients with non-GFPLA 3 .…”
mentioning
confidence: 80%
“…GFPLA is commonly associated with underling DM. Hyperglycemia is an important risk factor for GFPLA and poor control of DM plays a role in the development of GFPLA 2,5 . The clinical manifestations of GFPLA which usually include fever and right upper quadrant abdominal pain are not different from those of non-GFPLA 7 .…”
mentioning
confidence: 99%
“…Diabetic individuals are at increased risk of developing pyogenic liver abscess, in particular, KLA (2,3). DM is also an independent risk factor for KLA extrahepatic metastases (4).…”
Section: Discussionmentioning
confidence: 99%
“…DM is also an independent risk factor for KLA extrahepatic metastases (4). Extrahepatic seeding sites of KLA that have been documented include eyes, lungs, kidneys, skin/soft tissue, brain/meninges, and bones (2)(3)(4). Metastatic endophthalmitis is the most common involved complication, and often results in blindness or decreased vision of the affected eye (4,5).…”
Section: Discussionmentioning
confidence: 99%